TRANSFORMASI KEADAAN SOSIAL ANGGOTA JEMAAT MELALUI PELAYANAN DIAKONIA JEMAAT - Regina Oktavia; Abigael Maya Natalia, Theresya Tabangke, Juniati Rante Allo, Sarlota Pindan (ADISAM PUBLISHER, 2024)
This study aims to deepen the understanding of the Transformation of Social Conditions of Church Members Through Church Diakonia Services. The research adopts a mixed-methods approach by combining quantitative methods to investigate the impact of diakonia services on the social transformation of church members within the context of church life. Through in-depth interviews, surveys, and document analysis, the research will explore the motivations, barriers, and experiences of church members involved in diakonia services. Factors influencing active participation of church members, both spiritually and socially, will be identified and analyzed to comprehensively understand the dynamics of diakonia services. The study will also assess the impact of diakonia services on the transformation of social conditions, including changes in attitudes, the development of leadership skills, and spiritual growth. Additionally, the research will investigate the relevance of diakonia services in addressing social issues in the surrounding environment of the church. The findings of this research are expected to provide new insights into the role of diakonia services in achieving social transformation goals and their contribution to the church's mission and vision. The implications of this research can aid in the development of more effective and relevant service strategies to encourage positive transformation in the social conditions of church members and empower the church as an agent of change in society.